Community-engaged healthcare model for currently under-served individuals involved in the healthcare system - S.L. Barker; N. Maguire; R.E. Gearing; M. Cheung; D. Price; S.C. Narendorf; D.S. Buck (Elsevier, 2021)
In the US, many people are excluded from healthcare structures and systems, due to multiple macro and micro factors. Poverty, health ecosystems, mental health, and community amenities are some of the issues confronting those who are not able to access appropriate support. This population is often referred to as 'high needs, high cost' (HNHC), a term that has been applied to refer to people who repeatedly utilize services without significant benefit (we have replaced this term with 'currently under-served'; C-US). For many traditional health solutions may not address the fundamental issues confronting their health. Community-Engaged Healthcare (CEH) is an approach that equips members of the community to levy power to advocate for their own health or social solutions, designing their own interventions to address needs with support from health providers. A realist review was conducted to identify the existing literature around CEH. This yielded ten papers that were reviewed by at least two authors and rated in terms of quality. A model describing the processes underpinning CEH was then iteratively generated, resulting in additional terms that were used in a second review of the literature. A further 16 peer-reviewed articles were identified and were independently reviewed and quality rated. These articles were used to refine further iterations of the model and included in the review where appropriate. The resulting model schematically posits a set of relational factors identified to be important in the establishment of CEH. Notably, the transfer of autonomy and power over health decision-making processes is emphasized, which will require revolutionary thinking about how healthcare is delivered for patients.